Biomasa y densidad de dos especies de pastos marinos en el sur de Quintana Roo, México - Gutiérrez-Aguirre, Martha Angélica; de la Fuente-Betancourt, María Gabriela; Cervantes Martínez, Adrián (Revista de Biología Tropical, 2000)
The biomass and productivity of a seagrass community are useful for determining the ecological status of tbe eoast. Leaf biomass and shoot density in beds of Thalassia testudinum Banks & Sol. ex K. D. Koenig, were compared for two environments in the Mexican Caribbean coast (N= 6 quadrants/site) in November 1998. Shoot and leaf biomass values were lower in the mangrove-associated meadow than in the reef lagoon meadow. This could be related to the higher percentage of epiphytes on the leaves. In addition, T. testudinum had more biomass than Syringodium filiforme Kiitz in the reef lagoon